Eficácia do propofol e da associação de propofol e dexametasona no controle de náusea e vômito no pós-operatório de laparoscopia ginecológica - Ganem, Eliana Marisa [UNESP] (2002)
Background and Objectives - Gynecological laparoscopy is a procedure associated to a high incidence of postoperative nausea and vomiting (PONV). This study aimed at comparing the efficacy of propofol or propofol plus dexamethasone in preventing PONV in patients submitted to gynecological laparoscopy. Methods - Forty female patients, physical status ASA I and II aged 18 to 46 years, with no previous gastric complaint, undergoing diagnostic or surgical laparoscopy were randomly distributed in 2 groups: Group 1 - patients were given 2 ml IV saline solution, while Group 2 was given intravenous dexamethasone (8 mg), before anesthetic induction. All patients were premedicated with oral midazolam (7.5 mg) and induced with sufentanil (0.5 μg.kg -1) and propofol targed controlled infusion (BIS 60), with N 2O/O 2 (F 1O 2=0.4) for maintenance. Neuromuscular block was obtained with atracurium (0.5 mg.kg -1). Postoperative analgesia consisted of ketoprofen (100 mg) and butyl-eschopolamine plus dipirone. Patients were evaluated in the PACU and in the ward after 1, 2, 3 and 12 hours after PACU discharge. Results - Both groups were identical regarding demographics data as well as surgery and anesthesia duration. One Group 1 patient referred nausea in postanesthetic care unit and in the ward, and 3 patients referred vomiting in the ward. In Group 2 no patient referred nausea and vomiting, but the difference was not statistically significant. Conclusions - Propofol or propofol plus dexamethasone were efficient in preventing PONV in patients submitted to gynecological laparoscopy.